Sosialisasi Manajemen Keuangan Cerdas untuk Menghindari Pinjaman Online - Mintarsih, Mimin; Halim, Asep Abdul; Ayu, Nur (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
Technological advances have both good and bad impacts. One of the essential skills that must be possessed to achieve long-term financial success is the ability to manage personal finances wisely. Problems that are often faced in daily life, especially in the community in Mekarjaya Village, are difficulties in managing expenses, ignorance in planning a budget, consumptive living habits, lack of understanding of long-term investment and financial planning, accumulated debt problems, as well as lack of access or knowledge about the right financial products, so they are stuck with online loans. The activity method used PAR (Participacy Action Research) is through 3 stages (Planning, Implementation, Results and Evaluation). The results of this service activity include participants being able to understand how to manage finances intelligently and avoid illegal online loans.